2005
DOI: 10.7205/milmed.170.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobectomy for Refractory Epilepsy in the U.S. Military

Abstract: Epilepsy surgery outcomes in the U.S. military are similar to those reported from nonmilitary centers, with the majority of patients experiencing seizure remission and improvements in quality-of-life measures. Complete seizure remission after successful anterior temporal lobectomy enables some active duty military members to continue service in the U.S. Armed Forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…reported comparable findings in an epilepsy rehabilitation program not focused on epilepsy surgery. Similar to the results of our study, seizure outcome has been found as a relevant factor for postoperative employment in most studies, but not all studies . In those studies that found an influence of seizure outcome on postoperative employment it is not clear if complete freedom of seizures is a prerequisite for improvement of the employment situation or if a decreased seizure frequency or a lower seizure severity have an effect.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…reported comparable findings in an epilepsy rehabilitation program not focused on epilepsy surgery. Similar to the results of our study, seizure outcome has been found as a relevant factor for postoperative employment in most studies, but not all studies . In those studies that found an influence of seizure outcome on postoperative employment it is not clear if complete freedom of seizures is a prerequisite for improvement of the employment situation or if a decreased seizure frequency or a lower seizure severity have an effect.…”
Section: Discussionsupporting
confidence: 72%
“…Similar to the results of our study, seizure outcome has been found as a relevant factor for postoperative employment in most studies, 4,5,7,11,26,27,[35][36][37][38] but not all studies. 28,39,40 In those studies that found an influence of seizure outcome on postoperative employment it is not clear if complete freedom of seizures is a prerequisite for improvement of the employment situation or if a decreased seizure frequency or a lower seizure severity have an effect. Our data suggest that only those patients who are free of disabling seizures (Engel class I) will have employment gains.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in driving status was noted in 7–65% (median 48%) of patients depending on the study. Ability to drive was dependent on seizure freedom postsurgery (Reeves et al., 1997; Jones et al., 2002; Reid et al., 2004; Erickson et al., 2005; Asztely et al., 2007). Driving outcomes tended to be poorer in those who were older at the time of surgery (Britton et al., 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Surgical treatment for epilepsy can significantly improve the chances for seizure freedom (Erickson et al., 2005). However, patient‐related changes after epilepsy surgery may go beyond controlling seizures and include social factors such as employment, driving, social relationships, independence, and education.…”
mentioning
confidence: 99%
“…Subdural electrode recordings were performed in cases without a discernable temporal lobe abnormality on MRI. The characteristics, presurgical evaluation, and surgical outcomes of patients undergoing partial temporal lobectomy for refractory seizures at our center have been previously reported (13).…”
Section: Methodsmentioning
confidence: 99%